SEMIOTIKA DALAM TAFSIR SASTRA - Kuswarini, Prasuri (JURNAL ILMU BUDAYA, 2014)
This article is a literature review that discusses the semiotic approach to the study of literature.The discussion starts with notions about literature in general that say that literature is a work ofart that uses the medium of language and tells about life. However, as noted by some experts, oneof them is Eagleton, the use of language in literature often alienated or is not like its use ineveryday life. Based on such understanding, the explanation is done from a structural approachthat emphasizes the linguistic analysis, and ended with the discussion of Jakobson‟s poeticfunction of the language, which, at the same time, opens the talk about semiotic approach. Poeticfunction can be regarded as a bridge between linguistic analysis and aspects beyond language,such as emotion, psychology, ideology, etc, which plays an important role in the formation oflinguistic expression. Those aspects can then be analyzed more deeply with semiotic approach,because semiotics is the study of signs within social and cultural phenomena.Key words: literature, language, poetic function, semiotics